Sol i Stenhagen : projektering av en solcellsanläggning på Stenhagens bildnings- och kulturcentrum - Bergström, Albert; Hagstedt, Love; Holmsved, Love; Hägglund, Ludwig; Nyman, Joakim; Zetterberg, David (SLU/Dept. of Energy and Technology, 2017)
This is a thesis report written as a bachelor’s exam for Uppsala University, Sweden. In this paper, the possibilities of installing a photovoltaic system on a communal property in Uppsala is evaluated. Different systems were designed and simulated. It was found that the PV-system should not be smaller than 150 kWp due to a high self-consumtion-quota for a smaller system. The shortest payback period was achieved for a 157 kWp system and a 254 kWp system generates the highest yield after 20 years.